2001
DOI: 10.1128/jb.183.9.2795-2802.2001
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Functional and Structural Domains of Phosphorelay Histidine Kinase A of Bacillus subtilis

Abstract: The initiation of sporulation in Bacillus subtilis results primarily from phosphoryl group input into the phosphorelay by histidine kinases, the major kinase being kinase A. Kinase A is active as a homodimer, the protomer of which consists of an approximately 400-amino-acid N-terminal putative signal-sensing region and a 200-amino-acid C-terminal autokinase. On the basis of sequence similarity, the N-terminal region may be subdivided into three PAS domains: A, B, and C, located from the N-to the C-terminal end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 27 publications
(20 reference statements)
7
65
2
Order By: Relevance
“…S2 in the supplemental material). A PAS domain at the N terminus of B. subtilis KinA has a critical and indispensable role in the activity of the kinase (38,43).…”
Section: Resultsmentioning
confidence: 99%
“…S2 in the supplemental material). A PAS domain at the N terminus of B. subtilis KinA has a critical and indispensable role in the activity of the kinase (38,43).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the B. pertussis BvgAS and Bacillus subtilis Kin/ Spo phosphorelay systems have shown that sensor kinases, such as BvgS and Kin histidine kinases, form dimers prior to autophosphorylation (10,40). Given the similarity in domain structure between VieS and these sensor kinases, we predicted that VieS would also require dimerization for activity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when we analyze and compile all the information gathered from all the previous related studies (Hoch, 1993;Wang et al, 2001;Eswaramoorthy et al, 2009) and our present data, we are able to propose a novel hypothetical functional model of the sensor histidine-R E T R A C T I O N kinase A, which we purposely dubbed the "C-shaped intertwined model" or C-SIM (Figure 9). Simply put, based on our results, we speculate that only the PAS-B and PAS-B' domains of both monomers interact strongly leading to a stable dimer and enabling the necessary interaction between the PAS-A and the autokinase domains for phosphate transfer.…”
Section: Kina-gfp Transcriptional Fusionsmentioning
confidence: 99%